Economic growth versus economic development - Doina Dragoi (Atlantic Review of Economics (ARoEc), 2020)
The objective of this article is to approach the concepts of growth and economic development in order to highlight the essential aspects that differentiate them. These are fundamental concepts that define the economy of a nation and contribute for a better life for it. Economic growth does not lead to a high quality of education or technology, but contributes to increasing the added value of goods and services obtained within the sectors of a country's economy. The economic development aims at the economy of a country and implies the growth in both forms, qualitative and quantitative, including aspects related to the wealth of the people, includes aspects related to the wealth of people, their health, their education and good quality living conditions. Also, economic development can create opportunities in the field of employment and environmental conservation, in improving the literacy rate, eradicating poverty. The method is revising the specialized literature.
Keywords: O4; O1; 330; economic growth; economic development